EMPOWERING WOMEN THROUGH TRAINING ISLAMIC INHERITANCE LEARNING: A PROGRAM FOR MOTHERS IN THE MAJELIS TAKLIM - Uyuni, Badrah; Adnan, Mohammad; Majid, Zamakhsyari Abdul; Maarif, Samsul; Muhibudin, Muhibudin (The IMPACT : Jurnal Pengabdian Kepada Masyarakat Universitas Islam As-Syafiiyah, 2024)
This article highlights the crucial role of empowering women through education on Islamic inheritance within the context of Majelis Taklim, an Islamic study group in Indonesia. Given the diverse nature of inheritance laws influenced by cultural, religious, and customary variations, a comprehensive understanding becomes essential. The article explores the challenges the pluralistic legal system poses and its impact on family relationships and societal harmony. It presents a community service initiative dedicated to enhancing the knowledge of Majelis Taklim mothers on Islamic inheritance, aiming to empower them in understanding inheritance rights, imparting Islamic inheritance principles, and devising practical solutions for challenges often encountered. Utilizing a participatory and interactive approach, the article observes positive changes in the community's comprehension and application of Islamic inheritance principles. By exploring the impact of Islamic inheritance training on Majlis Taklim mothers, this article contributes valuable insights into the efficacy of community empowerment programs, specifically in increasing women's knowledge and involvement in Islamic legal matters.